The hemodynamic effect of simulated atrial fibrillation on left ventricular function - Stojadinović, Predrag; Deshraju, Aslesha; Wichterle, Dan; Fukunaga, Masato; Peichl, Petr; Kautzner, Josef; Šramko, Marek (Journal of cardiovascular electrophysiology, 2022)
INTRODUCTION: Atrial fibrillation (AF) is the most common sustained arrhythmia in humans. The onset of the arrhythmia can significantly impair cardiac function. This hemodynamic deterioration has been explained by several mechanisms such as the loss of atrial contraction, shortening of ventricular filling, or heart rhythm irregularity. This study sought to evaluate the relative hemodynamic contribution of each of these components during in vivo simulated human AF. METHODS: Twelve patients undergoing catheter ablation for paroxysmal AF were paced simultaneously from the proximal coronary sinus and the His bundle region according to prescribed sequences of irregular R-R intervals with the average rate of 90 and 130 bpm, which were extracted from the database of digital ECG recordings of AF from other patients. The simulated AF was compared to regular atrial pacing with spontaneous atrioventricular conduction and regular simultaneous atrioventricular pacing at the same heart rate. Beat-by-beat left atrial and left ventricular pressures, including LV dP/dT and Tau index were assessed by direct invasive measurement; beat-by-beat stroke volume and cardiac output (index) were assessed by simultaneous pulse-wave doppler intracardiac echocardiography. RESULTS: Simulated AF led to significant impairment of left ventricular systolic and diastolic function. Both loss of atrial contraction and heart rate irregularity significantly contributed to hemodynamic impairment. This effect was pronounced with increasing heart rate. CONCLUSION: Our findings strengthen the rationale for therapeutic strategies aiming at rhythm control and heart rate regularization in patients with AF.
Keywords: funkce levé komory srdeční; hemodynamika; Hemodynamics; kardiostimulace umělá; lidé; Catheter Ablation; fibrilace síní; Atrial Fibrillation; Humans; Ventricular Function, Left; Cardiac Pacing, Artificial; Heart Rate; srdeční frekvence; katetrizační ablace